(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SUMMARY: 1. The Medieval Age - 2. Becoming Modern - 3. Anglophone and Civilian - 4. Empire and Nation - 5. Global and Postmodern. ABSTRACT: There are many ways to understand the project of globalization as it unfolds in the twenty-first century. It is often viewed in terms of technological advance, finance and trade, or travel and communication. Each of these describe aspects of the project, yet none of its parts is more important than the legal basis upon which a regimen of global governance is being constructed. It is a legal regime of two parts, the coercive, or adjudicative and the persuasive, or educative. It involves the ordering of persons and things on a global scale as well as shaping the mind and thought of a global public. But the sources of this expansive framework of authority are neither recent nor modern. Instead, they are derived from two historic legal traditions, Anglophone and Civilian, as those traditions carry forward many accoutrements of the legal past. Among these are techniques and instruments for shaping human identity and human understanding in ways that fulfill the requirements of legal rule. In fact, the global project follows on a long tradition of employing religion as the educative instrument of governance. However, the new project of global rule is unprecedented in that it is intended to include all peoples in all regions of the earth. The project is also taking on a unique character, becoming Anglicized as the adaptability of Anglophone law subsumes many features of Civilian practice. But the great challenge is not only to impose judicial authority, it is also to instill attitudes of acceptance and habits of compliance among a global public. The purpose of what follows is to provide perspective on the project of globalization in both its adjudicative and educative aspects, with a special emphasis both on the use of technology to shape human understanding, and the use of religion as an instrument of legal rule. To do so this paper will focus on a broad historical context and on continuing historical themes in the development of a twenty-first century global law.